International practice and models in the appication of the “Smart city” concept and sustainable society - Tomić, Miloš (Sociološki pregled, 2023)
This concept is a standard in urban planning and transformation of services (transport, healthcare, education, security, ecology), the main characteristic of which is digitization, i.e., the application of modern information communication technology. The citizens’ adaptation to the modified conditions of the urban environment in which everyday problems are solved by technology leads to the formation of the so-called digital or smart nation, whose internal coherence and communication depend on the access to the Internet. This paper is aimed at describing key characteristics of smart cities and sustainable society, including practical examples of successfully transformed digital nations. The paper applies the content analysis technique and the historical- comparative analysis of the social digitization process.